Susan E. Poole. A Consideration of Gender Roles and Relations in the Aegean Bronze Age Interpreted from Gestures and Proxemics in Art - Dickinson , Oliver (Journal of Greek Archaeology, 2024)
This is a difficult book to review, partly because of the sheer mass of material covered. Besides the figures in the text, there are many more in the Part II downloadable from BAR (this contains 3 appendices listing figures from frescoes (905), from glyptic material (157), and three-dimensional items (31) that were considered, all given some description, also 17 tables). Surprisingly, only a few figurines out of the many from Aegean contexts receive much attention. The explanation may be found in the word “proxemics” in the title (a new word, to the reviewer), which means spatial interaction between individuals; but interesting evidence is offered by some classes of figurine for the interpretation of gestures and poses, and this does receive some attention. The difficulties of coping with this mass of material and the discussion of it are compounded by the lack of an index, typical of BAR but making consultation and checking of references to a wide range of instances and to complex theoretical approaches a lengthy and often frustrating business.